2019
DOI: 10.3847/1538-4357/ab3b06
|View full text |Cite
|
Sign up to set email alerts
|

Double Neutron Star Mergers from Hierarchical Triple-star Systems

Abstract: The isolated binary evolution model for merging neutron stars (NSs) involves processes such as mass transfer, common-envelope evolution, and natal kicks, all of which are poorly understood. Also, the predicted NS-NS merger rates are typically lower than the rates inferred from the LIGO GW170817 event. Here, we investigate merger rates of NS and black hole (BH)-NS binaries in hierarchical triple-star systems. In such systems, the tertiary can induce Lidov-Kozai (LK) oscillations in the inner binary, acceleratin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 153 publications
(198 reference statements)
0
22
0
Order By: Relevance
“…These chirp mass and eccentricity measurements will make it possible to distinguish at least a fraction of the better-measured eccentric DNSs from the much larger Galactic DWD population. They can also elucidate the origin of the DNS systems: although the isolated binary channel is generally assumed to dominate DNS formation, with globular clusters expected to contribute less than 10 per cent of all merging DNSs (Phinney 1991; Grindlay et al 2006;Ivanova et al 2008;Kremer et al 2018), recent work has suggested that dynamical or three-body formation channels may be relevant (Hamers & Thompson 2019;Andrews & Mandel 2019). Moreover, LISA's measurement of the eccentricity distribution in the early DNS evolutionary history could shed light on uncertainties in models of isolated binary evolution, such as the stability of case BB mass transfer.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These chirp mass and eccentricity measurements will make it possible to distinguish at least a fraction of the better-measured eccentric DNSs from the much larger Galactic DWD population. They can also elucidate the origin of the DNS systems: although the isolated binary channel is generally assumed to dominate DNS formation, with globular clusters expected to contribute less than 10 per cent of all merging DNSs (Phinney 1991; Grindlay et al 2006;Ivanova et al 2008;Kremer et al 2018), recent work has suggested that dynamical or three-body formation channels may be relevant (Hamers & Thompson 2019;Andrews & Mandel 2019). Moreover, LISA's measurement of the eccentricity distribution in the early DNS evolutionary history could shed light on uncertainties in models of isolated binary evolution, such as the stability of case BB mass transfer.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Significant orbital eccentricities may be imparted to DNSs by supernova kicks (e.g., Tauris et al 2017) or Blaauw kicks (Blaauw 1961). Short-period DNSs may also be formed through dynamical hardening interactions in globular clusters until the binary is ejected into the field, presents too small of a cross-section for further interactions, or merges through GW emission (Kulkarni et al 1990;Phinney & Sigurdsson 1991), or in hierarchical triple-star systems (Hamers & Thompson 2019). The typical separation of the ejected DNSs depends on the globular cluster properties, but may fall in the range of a few solar radii, or orbital frequencies of a few times 10 −5 Hz (Andrews & Mandel 2019).…”
Section: Eccentricitymentioning
confidence: 99%
“…However, it is still possible that some of the DNSs in the observed sample were formed through an alternative evolutionary channel (e.g. Hamers & Thompson 2019;Andrews & Mandel 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This could take the form of dynamically induced mergers in dense stellar environments, such as globular clusters (Andrews & Mandel 2019 but see, e.g., Ye et al 2020). Meanwhile, Kozai–Lidov oscillations (Kozai 1962; Lidov 1962) in hierarchical triple systems can drive up the eccentricity of the inner binary (see Naoz et al 2016 for a review) and contribute to the formation of merging DNSs (Hamers & Thompson 2019). Both types of dynamical encounters can change the binary orbital evolution, including the eccentricity.…”
Section: Discussionmentioning
confidence: 99%